Network-on-Chip implementation of Midimew-Connected Mesh Network - Awal, Md. Rabiul; Rahman, M.M. Hafizur (IEEE Computer Society, 2013)
Architecture of interconnection network plays a significant role in the performance and energy consumption of Network-on-Chip (NoC) systems. In this paper we propose NoC implementation of Midimew-connected Mesh Network (MMN). MMN is a Minimal Distance Mesh with Wrap-around (Midimew) links network of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher-level networks. For implementing all the links of level-3 MMN, minimum 4 layers are needed which is feasible with current and future VLSI technologies. With innovative combination of diagonal and hierarchical structure, MMN possesses several attractive features including constant node degree, small diameter, low cost, small average distance, and moderate bisection width than that of other conventional and hierarchical interconnection networks.